Von Neumann-Jordan constant, James constant, and Dunkl-Williams constant for small Morrey spaces - Mu'tazili, Aqfil; Gunawan, Hendra (KOMUNITAS Analisis Matematika INDONESIA, 2022)
In this article, we compute Von-Neumann-Jordan constant, James constant, and Dunkl-Williams constant for small Morrey spaces. We find that the three constants are the same as those for the classical Morrey spaces.